Electric field control of magnetic properties and electron transport in BaTiO3-based multiferroic heterostructures. (27th November 2015) - Asa, M; Baldrati, L; Rinaldi, C; Bertoli, S; Radaelli, G; Cantoni, M; Bertacco, R
Abstract: In this paper, we report on a purely electric mechanism for achieving the electric control of the interfacial spin polarization and magnetoresistance in multiferroic tunneling junctions. We investigate micrometric devices based on the Co/Fe/BaTiO3 /La0.7 Sr0.3 MnO3 heterostructure, where Co/Fe and La0.7 Sr0.3 MnO3 are the magnetic electrodes and BaTiO3 acts both as a ferroelectric element and tunneling barrier. We show that, at 20 K, devices with a 2 nm thick BaTiO3 barrier present both tunneling electroresistance (TER = 12   ±   0.1%) and tunneling magnetoresistance (TMR). The latter depends on the direction of the BaTiO3 polarization, displaying a sizable change of the TMR from  −0.32   ±   0.05% for the polarization pointing towards Fe, to  −0.12   ±   0.05% for the opposite direction. This is consistent with the on-off switching of the Fe magnetization at the Fe/BaTiO3 interface, driven by the BaTiO3 polarization, we have previously demonstrated in x-ray magnetic circular dichroism experiments.